2016
DOI: 10.1155/2016/6239434
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Gastrointestinal Parasitic Infections among Young Population in Northeast Brazil

Abstract: Background. Intestinal parasitic infections constitute a major public health problem that is frequently associated with poverty, inadequate sanitation, and the nutritional status of the population. Objective. The aim of the present study is to investigate the possible association of parasitic infections, sanitary conditions, hygiene practices, and the nutritional and socioeconomic status of a poor youth population. Methods. A cross-sectional study was conducted with 367 children and adolescents inhabiting a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
1
4
0
2
Order By: Relevance
“…This prevalence of hookworm infections was lower compared to 45% and 29.4% in earlier reports in Ghana and Ibadan [32,33]. However, da Silva et al ( 2016) agreed with the findings of our report [19]. This reduction of hookworm (Ancylostoma duodenale/Necator americanus) prevalence could be indicative of a successful control measures intervention, mass drug administration and health enlightenment programs.…”
Section: Resultssupporting
confidence: 84%
“…This prevalence of hookworm infections was lower compared to 45% and 29.4% in earlier reports in Ghana and Ibadan [32,33]. However, da Silva et al ( 2016) agreed with the findings of our report [19]. This reduction of hookworm (Ancylostoma duodenale/Necator americanus) prevalence could be indicative of a successful control measures intervention, mass drug administration and health enlightenment programs.…”
Section: Resultssupporting
confidence: 84%
“…A associação das parasitoses intestinais à pobreza generalizada mostra-se um problema social relevante. Os acessos aos serviços de saneamento e saúde necessitam estar no centro das discussões de políticas públicas efetivas, e de maneira a atender as pessoas que vivem em condições insalubres, a fim de garantir melhor qualidade de vida para essa população (SILVA et al 2016).…”
Section: Introductionunclassified
“…This result was similar to studies conducted in the municipal education system in the municipality of Cascavel, state of Paraná (4.2%) (Martinichen-Herrero & Lenartovicz, 2013), and a daycare center in the city of Tubarão, state of Santa Catarina (1.3%) (Batista, et al, 2009). Other studies in the northeastern region of Brazil have reported T. trichiura as the most prevalent helminth (12% and 51.5%) (da Silva, et al, 2016;Lander, et al, 2012). These high rates of prevalence may be due to the common fecal-oral cycle of both helminths.…”
Section: Discussionmentioning
confidence: 88%